The Influence of Capital Intensity, Institutional Ownership, Firm Size and Public Share Ownership on Accounting Conservatism (In Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2014 – 2023) - Maahury, Ranny Gabriella; Berliani, Kartika (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
In order to ascertain the impact of capital intensity, institutional ownership, firm size, and public share ownership on accounting conservatism, the study was carried out on manufacturing companies in the food and beverage sub-sector that were listed on the Indonesia Stock Exchange between 2014 and 2023. A quantitative method with a descriptive and verificative approach is the research methodology employed. Financial statements of food and beverage manufacturing companies listed on the Indonesia Stock Exchange between 2014 and 2023 comprise the data used. The findings of the t-test indicate that, although Institutional Ownership and Firm Size have no effect on Accounting Conservatism, Capital Intensity and Public Share Ownership do. Capital Intensity, Institutional Ownership, Firm Size, and Public Share Ownership all significantly impact accounting conservatism, according to the simultaneous test results.